Justification for a self-regulated learning training program for higher education students in massive open online courses - Cao-Tuong Dinh; Hoang-Yen Phuong (Institute of Advanced Engineering and Science, 2026)
Self-regulated learning (SRL) has been well documented in the literature for its benefits for students’ learning success. However, there is still a dearth of imperial intervention that helps promote students’ self-regulation, and a theoretical justification for such a program is essential. To date, literature has shown three prominent theories: social cognitive, social-cultural, and cognitive constructivist. The goal is to explore the conceptualization of SRL, which, despite it is long history, lacks a universally accepted definition. We analyze these theories and their models to determine which best supports the design of a SRL strategy intervention for university students in massive open online course (MOOC) environments. Based on this analysis, we propose a working definition of SRL that fits the unique demands of MOOCs. The results suggest that the social-cognitive theory offers the most suitable framework, as it integrates cognitive, metacognitive, motivational, and social aspects of learning. Additionally, it provides a practical model of strategies that can be implemented in MOOC-based learning environments.